Chemoselectivity in Gold(I)-Catalyzed Propargyl Ester Reactions: Insights From DFT Calculations - Sun, Qing; Hong, Pan; Wei, Dongdong; Wu, Anan; Tan, Kai; Lu, Xin (Frontiers in Chemistry, 2019)
Au-catalyzed propargyl ester reactions have been investigated by a comprehensive density functional theory (DFT) study. Our calculations explain the experimental observed chemoselectivity of Au-catalyzed propargyl ester reactions very well by considering all possible pathways both in the absence and presence of 1,2,3-triazole (TA). The “X-factor” of TA is disclosed to have triple effects on this reaction. First of all, it can stabilize and prevent rapid decomposition of the Au catalyst. Secondly, the existence of TA promotes the nucleophilic attack and alters the chemoselectivity of this reaction. Moreover, TA acts as a “relay” to promote the proton transfer.